Peran Kyai dalam Membentuk Kemandirian Santri Broken Home - Sulaiman Sulastri; Badrus (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
A Kiai has a significant role in education in pesantren. Santri will imitate the nature and behaviour of a Kiai who educates him. So a Kiai must instil good moral values following Islamic teachings and an honest attitude that must plant as early as possible in a santri. This research is qualitative research with case study research—data collection techniques using in-depth interviews, observation and documentation. The results show that the kyai has a strategic role in shaping the independence of the santri in the form of love, motivation, discipline, patience and reading the Qur'an.